Case report: Regression after low-dose glucocorticoid therapy in a case of acute immune myocarditis induced by anti-PD-1 therapy for NSCLC - Chen, Liqianqi; Zhang, Suihao; Gong, Long; Zhang, Yucong (Frontiers in Oncology, 2024)
Background: PD-1 inhibitors exhibit efficacy in managing unresectable/metastatic driver gene-negative NSCLC, albeit with potential immune-related adverse events (irAEs). Among these, immune checkpoint inhibitor-associated myocarditis (ICI-M)is rare yet lethal. This study presents the initial successful instance of ICI-M in a lung cancer patient, rescued by low-dose glucocorticoids post-deterioration during treatment.Case Summary: A 78-year-old male with a medical history of stage IV pT3N2M1 NSCLC underwent four cycles of palliative chemotherapy, resulting in stable disease (SD). Subsequent to declining further chemotherapy, the patient was transitioned to a targeted therapy regimen comprising Anlotinib in conjunction with PD-1 inhibitor immunotherapy. On the 26th day post-administration of the PD-1 inhibitor, the patient manifested Grade 2 immune-mediated myocarditis. Treatment encompassing 1mg/kg methylprednisolone combined with immunoglobulin shock therapy was initiated for 3 days, achieving symptomatic control. Nonetheless, upon tapering methylprednisolone dosage to 4-8mg/3-4d, the condition deteriorated, necessitating transfer to the intensive care unit. Methylprednisolone dosage was escalated to 80mg/day for 3 days, followed by gradual reduction by one-third to two-thirds weekly, culminating in the patient's safe discharge from the hospital. Conclusion: Immune-related myocarditis linked to checkpoint inhibitors is often managed effectively with high-dose glucocorticoid therapy. However, in Asian populations, low-dose glucocorticoids are increasingly utilized for salvage therapy, yielding favorable outcomes and improving prognosis compared to European populations.